Aktorzy polityczni i media w procesie zarządzania informacją = Political actors and mass media in process of information management - Arkuszewska, Daria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Article is devoted to management of political information. Author tries to explain how process of information management is used by politicians and mass media. Both of them need each other to exist and to produce news. Politicians use mass media to inform the community, and mass media gain profit from spreading that information. Politicians seek to control some part of the news that is the consequence of their political interest. Examples of information management are gatekeeping and information priorities. Politics has always been the main topic of newscasts. Currently newscast are made in the different way in a different way that in the past. Article contains examples of information management taken from Polish policy and mass media area.
Keywords: zarządzanie informacją; media; polityka